Population assemblages of a termite species, Macrotermes gilvus Hagen (Blattodea: Termitidae) at different land uses - Lin, Chai Wen; Mohktar, Anis Syahirah; Wan Abdul Ghani, Wan Mohd Hafezul (Penerbit Universiti Kebangsaan Malaysia, 2024)
Several studies were conducted on the distribution of Macrotermes gilvus Hagen (Blattodea: Termitidae) especially in northern part of Peninsular Malaysia. However, information on distribution of this termite species in different type of landscapes was scarcely reported. Therefore, a study was conducted to investigate the M. gilvus population and distribution in different land uses as well as the variation of mound size based on different areas. Four areas of different land use in Universiti Putra Malaysia, Selangor, Malaysia; oil palm plantation, landscaped garden, farmland, and urban area were selected to survey the quantity and size of their mounds as well as the population of M. gilvus. For each area, three M. gilvus mounds from three size categories: small (height of 1 to 20 cm; diameter of 1 to 50 cm), medium (height of 21 to 40 cm; diameter of 51 to 80 cm), and large (height of 41 to 60 cm; diameter of 81 to 120 cm) were randomly selected. The result of this study shows that oil palm plantation has the highest number of mounds and population density of M. gilvus (51.4% and 845882.35 individual per ha), followed by landscaped area (35.5% and 401940.00 individual per ha). The farmland recorded the lowest number of mound and population density (13.1% and 164385.59 individual per ha), meanwhile the species was absent in urban area. All areas except the urban setup were significantly dominated with large size of mounds, followed by medium size mounds and the least was small size of mounds. This study concluded that the species preferred to inhabit the shaded area, dense-canopy cover with less human activities and buildings, which provided the species a good area to build mound and foraging for food.